The Baby Doe Rule: Still a Threat - Moskop, John C. (The Hastings Center report, 1986)
Current federal policy, as reflected in the final Baby Doe rule, will have a chilling effect on the ability of doctors to care appropriately for severely disabled infants. The policy threatens to prolong life unjustifiably for such infants. It will force physicians to violate a duty to do no harm without compensating benefit. And it raises serious problems for the just distribution of health care.